J.CO Coffee & Donuts Marketing Strategy - Aulia Riski Ayu Putri; Indah Khoirun Nisa; Lim Hui Yee; Daisy Mui Hung Kee; Koo Hui Min; Lee Sing Yi; Liu Jie Xin (AIBPM Publisher, 2020)
J. CO Donuts & Coffee is a franchise of cafÃ© restaurant chains that sell donuts, coffee and frozen yogurt. The company is owned by Johnny Andrean Group. Since 2005, J.CO Donuts & Coffee becomes the fastest growing donut & coffee chain in Indonesia. They have successfully penetrated into the local market in Indonesia against Krispy Kreme and Dunkin Donuts. They also have been rapidly expanding their store chains throughout South East Asia countries such as Malaysia, Singapore, Philippines, and Hong Kong. Analysis of J.CO Donuts & Coffee will be done to know more on the position of the company in the market. SWOT analysis is needed to know JCO Donuts & Coffee marketing situation.